2015
DOI: 10.1021/acs.inorgchem.5b01040
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Imines, Nitriles, and Isocyanides with Pentaphenylborole: Coordination, Ring Expansion, C–H Bond Activation, and Hydrogen Migration Reactions

Abstract: The reactions of pentaphenylborole with imines, isocyanides, and acetonitrile were investigated experimentally and theoretically. On the basis of literature precedent, we envisioned that the dipolar substrates would undergo facile ring expansion reactions to yield new BNC5 heterocycles. For acetonitrile and one particular imine, this ring expansion process was observed. However, in many cases, unexpected reactivity occurred. This included hydride migration of an imine ring expanded product and the ortho C-H bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 76 publications
(114 reference statements)
0
59
0
Order By: Relevance
“…Being an isolable antiaromatic compound class, boroles have received growing interest in recent years . Due to their peculiar electronic situation, they feature intriguing reactivity including E−H bond splitting, cycloadditions and ring expansions, as well as Lewis acidity enabling adduct formation even with weak Lewis bases such as CO …”
Section: Introductionmentioning
confidence: 99%
“…Being an isolable antiaromatic compound class, boroles have received growing interest in recent years . Due to their peculiar electronic situation, they feature intriguing reactivity including E−H bond splitting, cycloadditions and ring expansions, as well as Lewis acidity enabling adduct formation even with weak Lewis bases such as CO …”
Section: Introductionmentioning
confidence: 99%
“…[6] The strong electron-acceptinga bility and high electron affinity of boroles suggest that they may have potentiala sc andidates for electron-transporting and-accepting materials in organicl ightemitting diodes (OLEDs)a nd photovoltaics (OPVs). The strongL ewis acidity of boroles and their propensityt oa dd most nucleophiles to the endocyclic boron centeri sd ue to the presence of the low-lying empty po rbital at the boron center,a long with their antiaromaticity, [4c, 5, 6b, c, 8] whichm akes them very reactive toward acetonitrile, [9] azides, [10] sulfur, [11] amines, [12] isothiocyanates, [13] and CO. [14] Studies have shown that boroles are useful forc ertain s-bond activation reactions, in particular the cleavage of SiÀH [15] and dihydrogen bonds. The variety of different reactivity patterns includes Lewis-pair formation, small molecule activation,D iels-Alder cycloadditions,a nd ring expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The variety of different reactivity patterns includes Lewis-pair formation, small molecule activation,D iels-Alder cycloadditions,a nd ring expansion. [3g, 4d, 6b, 14b, 17] Recently,b oroles have also shown a propensity to undergo ring expansion reactionsw ith other unsaturated species, [9,10,13,18] leading,n otably,t o1 ,2-azaborinine compounds, BN-isosteres of benzene of significant current interestf or their pharmaceutical, materials, and hydrogen-storage properties. [16] Similartoother cyclopentadienesystems, boroles can also undergo Diels-Alder reactions with alkenes [4d] and alkynes.…”
Section: Introductionmentioning
confidence: 99%
“…23,49,58 Alternatively, N--methylmorpholine--N--oxide (NMMO) proved to be an effective oxygen atom source. 67 This species dimerizes to 39 through intermolecular dative B,N contacts that are resilient in solution and the solid--state. 58 Interestingly, computational analyses indicate that 1,2--oxaborines have aromatic character approaching the magnitude of 1,2--azaborines.…”
mentioning
confidence: 99%
“…59 The mechanism to form these species was rationalized via oxygen coordination (Int20), followed by the formation of bicyclic intermediate Int21 via intramolecular attack of the butadiene to the carbon of the nitrone and a subsequent B--C bond cleavage. 67 An imine with two phenyl groups on the α--carbon and a benzyl group on nitrogen formed a stable adduct (49). Such eight--membered cyclic compounds are difficult to prepare and are unusual examples of BNOC 5 rings.…”
mentioning
confidence: 99%